The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/0004-282x20180061
|View full text |Cite
|
Sign up to set email alerts
|

Everything you always wanted to know about sex and Neurology: neurological disability and sexuality

Abstract: Disability proved to be the main variable related to the presence of sexual dysfunction. Patients with ALS had the worst rates of sexual dysfunction. Patients with MS were similar to the control group. As for the PD group, no patient had normal sexuality. Finally, in stroke patients, the presence of comorbidities and their treatment may have negatively influenced sexuality. These findings showed that patients with chronic neurological diseases have sexual dysfunction and underscore the need for neurologists to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 32 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…The prevalence of SD after stroke ranges from 20 to 95%, occurring in either gender ( 12 , 13 ). Nasimbera et al ( 14 ) reported that SD in both sexes was present in 75% of post-stroke patients, whereas the prevalence of SD in the healthy controls was only 22.5%. A national population-based study including both genders showed that sexual activity was significantly lower in patients with stroke than in those without stroke (60 vs. 30.8%) ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of SD after stroke ranges from 20 to 95%, occurring in either gender ( 12 , 13 ). Nasimbera et al ( 14 ) reported that SD in both sexes was present in 75% of post-stroke patients, whereas the prevalence of SD in the healthy controls was only 22.5%. A national population-based study including both genders showed that sexual activity was significantly lower in patients with stroke than in those without stroke (60 vs. 30.8%) ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…173 However, it can still be considered a "hidden" symptom of MS, with estimates of prevalence ranging up to almost 80% of MS patients. 112,113,114,115,116 Sexual dysfunction may be underreported as neurologists do not address it with even a general question in half of cases, and patients may not independently address the topic with their neurologists if not asked. Therefore, assessment of sexual dysfunction primarily involves a semi-structured clinical interview, with focus on identification followed by assessment of severity and impact on quality of life.…”
Section: Sexual Dysfunctionmentioning
confidence: 99%
“…Amyotrophic lateral sclerosis (ALS) is a progressive disorder of motor neurons in the brain and spinal cord [33]. ALS patients were found to have problems with their sexual relationship due to impaired sexual function such as decreased libido [34], with studies indicating that ALS had the worst rates of SD when compared with other NLDs [35]. Shahbazi et al [36] reported that although SD affected the QoL in ALS patients, 75% of their clinicians were not familiar with any strategies or interventions to help the patients.…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%